2018
DOI: 10.1080/16549716.2018.1477249
|View full text |Cite
|
Sign up to set email alerts
|

Building oral health research infrastructure: the first national oral health survey of Rwanda

Abstract: Background: Oral health affects quality of life and is linked to overall health. Enhanced oral health research is needed in low- and middle-income countries to develop strategies that reduce the burden of oral disease, improve oral health and inform oral health workforce and infrastructure development decisions. Objective: To implement the first National Oral Health Survey of Rwanda to assess the oral disease burden and inform oral health promotion strategies. Methods: In this cross-sectional study, sample siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Nearly two-thirds (63.9%) had experienced painful aching in the mouth within the past 12 months. For those ages 20 years and above, over 50% of the participants reported that oral health problems were affecting their quality of life [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nearly two-thirds (63.9%) had experienced painful aching in the mouth within the past 12 months. For those ages 20 years and above, over 50% of the participants reported that oral health problems were affecting their quality of life [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…The data provided by the NOHSR afforded the opportunity to assess factors related to oral disease. Building on the first manuscript describing the NOHSR [ 15 ], we further analyzed the NOHSR dataset to investigate key outcome and descriptive variables to better understand the oral health of the surveyed population. Specifically, we investigated oral health indicators in relation to demographic information, personal oral hygiene practices, and oral health quality of life indicators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-income countries fill the gap by conceptualizing, coordinating, and funding African studies, and the resultant effect at times is the promotion of trials that are not of critical importance to Africa’s health care problems. 5 - 7 …”
Section: Collaboration Among Sites To Harmonize Treatment Guidelines mentioning
confidence: 99%